1983
DOI: 10.1103/physrevc.28.1431
|View full text |Cite
|
Sign up to set email alerts
|

C11level structure via theB

Abstract: The reaction ' B(p, y}"C has been investigated in the energy range E~=0.07 -2.20 MeV. The broad resonant structure previously observed in the ground state transition near E"=1. 2 MeV has been seen also in y-ray transitions to excited states. The observed excitation functions as well as the y-ray angular distributions can be explained by assuming several broad overlapping resonances.The low-energy data (Ep & 0.6 MeV) reveal the existence of two s-wave resonances at Ep =0.010 and 0.56 MeV. Spectroscopic factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
4

Year Published

1987
1987
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 34 publications
2
53
0
4
Order By: Relevance
“…(c) is for the 9.20-MeV resonance, where we also found a small peak in the spectrum. We used J π = 5/2 + and the total width Γ tot =500 keV from a previous measurement [17], although such a large Γ tot was inconsistent with our R-matrix analysis. (d) is for the 9.97-MeV resonance, which was identified as a strong alpha resonance in the spectrum.…”
Section: Astrophysical Reaction Rate Of 7 Be(α γ)mentioning
confidence: 99%
“…(c) is for the 9.20-MeV resonance, where we also found a small peak in the spectrum. We used J π = 5/2 + and the total width Γ tot =500 keV from a previous measurement [17], although such a large Γ tot was inconsistent with our R-matrix analysis. (d) is for the 9.97-MeV resonance, which was identified as a strong alpha resonance in the spectrum.…”
Section: Astrophysical Reaction Rate Of 7 Be(α γ)mentioning
confidence: 99%
“…9.645±50 956 (3/2 − ) 210±40 (γ,p,α) [9] (8) 9.780±50 1091 (5/2 − ) 240±50 (γ,p) [25] (9) 9.970±50 1281 (7/2 − ) 120±20 (γ,p) [25] (10) 10.083±5 1394 7/2 + ∼230 (γ,p,α) [25] The observed peak corresponding to the two unresolved levels (3)+(4) has been fitted by considering the broadening due to the energy resolution. The fitting function is expressed in terms of the incoherent sum of two Breit-Wigner shapes bw(E) (3) , bw(E) (4) , plus an additional term describing the contribution of the tail of the resonant level at 9.2 MeV, bw(E) (5) , and a non resonant term p(E):…”
Section: Analysis Of the E11 C Excitation Energy Spectramentioning
confidence: 99%
“…The cross section of the 10 B(p,α 0 ) 7 Be reaction has been investigated in many different experiments, direct [7][8][9][10][11][12][13] and indirect [14][15][16], and it has been calculated using DWBA and potential model [17]. Reviews of the data are reported in [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The 11 B(p,α) 8 Be −→ αα reaction is one of the main candidates for aneutronic energy production in plasma-induced fusion reactors [1]. Natural boron consists of 11 B (80.1%) and 10 B (19.9%) and the (p,α) reaction on 10 B represents a contaminant for aneutronic fusion, since it produces the radioactive nucleus 7 Be.…”
Section: Introductionmentioning
confidence: 99%